2013
DOI: 10.1016/j.astropartphys.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of the time stability of the half-life of alpha-decay 214Po nuclei

Abstract: A method and results of an experimental test of the time stability of the half-life of alpha-decay 214 Po nuclei are presented. Two underground installations aimed at monitoring the time stability have been constructed. Time of measurement exceeds 1038 days for one set up and 562 days for the other. It was found that amplitude of possible annual variation of 214 Po half-life does not exceed 0.2% of the mean value. The limit on the deviation of the decay curve from exponent at 0.034 · T 1/2 < t < 0.1 · T 1/2 ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Experimental research of the half-life time stabilities of 214 Po (October 2012 -May 2015, TAU-1 and TAU-2 setups) [1,2,3] and 213 Po (Julay 2015 up to now, TAU-3 setup) [4] carry out at the Baksan Neutrino Observatory of the INR RAS. A half-life defines as a result of analysis of the decay curves constructed from a set of life-time values of separate nuclei of the exploring isotope.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research of the half-life time stabilities of 214 Po (October 2012 -May 2015, TAU-1 and TAU-2 setups) [1,2,3] and 213 Po (Julay 2015 up to now, TAU-3 setup) [4] carry out at the Baksan Neutrino Observatory of the INR RAS. A half-life defines as a result of analysis of the decay curves constructed from a set of life-time values of separate nuclei of the exploring isotope.…”
Section: Introductionmentioning
confidence: 99%
“…The basic framework of quantum mechanics is disturbed without modification to the Schrödinger equation for a position dependenth, or by imposing special conditions of some sort. Inspecting (20) and (22), one might consider special conditions on the forms ofh or ψ so the additional terms are zero, and the operator becomes "effectively Hermitian". It is worth mentioning there is ongoing work on non-Hermitian and complex Hamiltonians being used to describe dissipative and open systems [35,36].…”
Section: Symmetrized Hermitian Frequency Operator F H and Modified Scmentioning
confidence: 99%
“…It should be mentioned that there have been studies in which it was concluded there was no gravitational dependence to the decay rate oscillations [20,21]. There is also dispute in the literature concerning the reality of the decay rate oscillations [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The construction of the TAU-3 facility with a 229 Th source is similar to TAU-1 and TAU-2 [1]. It comprises a scintillation detector D1, a plastic scintillator (PS), which is made of two disks d = 18 mm and h = 1 mm glued together.…”
Section: The Facility Descriptionmentioning
confidence: 99%
“…Experimental studies of 214 Po half-life time dependence (τ ) [1][2][3] have been carried out at the Baksan Neutrino Observatory of the Institute for Nuclear Research of the Russian Academy of Sciences since 2008. Unlike studies on determining the half-life by the results of analysis of time dependence of the explored isotope activity, decay curves analyzed at the Observatory are plotted based on a set of data on lifetimes of separate nuclei of the 214 Po isotope.…”
Section: Introductionmentioning
confidence: 99%